2015
DOI: 10.1016/j.epsl.2015.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic speed limits from plate kinematic reconstructions

Abstract: Editor: Y. Ricard Keywords: RMS plate velocities plate reconstructions continent and craton speedsThe motion of plates and continents on the planet's surface are a manifestation of long-term mantle convection and plate tectonics. Present-day plate velocities provide a snapshot of this ongoing process, and have been used to infer controlling factors on the speeds of plates and continents. However, present-day velocities do not capture plate behaviour over geologically representative periods of time.To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 50 publications
11
81
1
Order By: Relevance
“…This indicates that the forcing by downgoing plates older than ~50 m.y. is generally sufficiently large to overcome other forces (e.g., by the upper plate or the convective mantle) that may impede trench motions, consistent with the long-standing conclusion that the downgoing plate pull is the primary force driving plate motions (Forsyth and Uyeda, 1975;Zahirovic et al, 2015). A recent global dynamic modeling study also concluded that subducting plates provide the main forces that drive formation and migration of plate boundaries (Mallard et al, 2016).…”
Section: Variable Styles Of Slab Transition Zone Interactionsupporting
confidence: 62%
See 2 more Smart Citations
“…This indicates that the forcing by downgoing plates older than ~50 m.y. is generally sufficiently large to overcome other forces (e.g., by the upper plate or the convective mantle) that may impede trench motions, consistent with the long-standing conclusion that the downgoing plate pull is the primary force driving plate motions (Forsyth and Uyeda, 1975;Zahirovic et al, 2015). A recent global dynamic modeling study also concluded that subducting plates provide the main forces that drive formation and migration of plate boundaries (Mallard et al, 2016).…”
Section: Variable Styles Of Slab Transition Zone Interactionsupporting
confidence: 62%
“…Most Cenozoic downgoing plate motions range between ~5 and 10 cm/yr (Sdrolias and Müller, 2006;Müller et al, 2008;Goes et al, 2011;Zahirovic et al, 2015), and there is a correlation of increasing velocity with the age of the plate at the trench (Carlson et al, 1983;Lallemand et al, 2005;Goes et al, 2011). This range and the age trend have been interpreted as an expression of upper-mantle slab pull as driving force of the plates (Conrad and LithgowBertelloni, 2002;Faccenna et al, 2007;Goes et al, 2011).…”
Section: Plate Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSP was the fastest-moving plate during Cenozoic times (Zahirovic et al 2015). Today, the absolute motion of its southern part (∼10 cm/year) in classical reference frames (DeMets et al 2010;Seton et al 2012or Kreemer et al 2014) is comparable to that of the Pacific Plate, which is presently the fastest plate in the world.…”
Section: Present-day Boundaries Of the Pspmentioning
confidence: 99%
“…11: Africa absolute velocity (Doubrovine et al 2012;Gaina et al 2013) based on moving hot spots and a true polar wander model before 124 Ma. 12: Africa RMS velocity, hybrid moving hotspots, and true polar wander corrected reference frame (Zahirovic et al 2015). 13: Africa-Eurasia convergence velocity at the longitude of Oman ).…”
Section: Africa From Mantle Plumes To Subductionmentioning
confidence: 99%